Penerapan Pembelajaran Berorientasi NoS (Nature of Science) untuk Meningkatkan Keterampilan Proses Sains dan Pemahaman Konsep Siswa - Jumaeni, Jumaeni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The results of observations carried out at SMA Negeri 1 Pemenang, North Lombok Regency, found that the classical completeness obtained was far from the predetermined indicators. The low student learning outcomes are thought to occur because presentations often use the lecture method and there are no practical activities because the tools for this are not available. Apart from that, in every lesson that uses the lecture method the teacher is often the center of attention and the students are only the receiving objects. So students do not have the opportunity to develop knowledge and abilities in science process skills. The NoS (Nature of Science) model invites students to be able to train students' abilities in improving problem-solving abilities so that they can improve students' science process skills and understanding of concepts. The aim of this research is to improve students' science process skills and conceptual understanding through the NoS (Nature of Science) learning model on the sub-subject of environmental pollution. This type of research is classroom action research carried out in 2 cycles consisting of planning, implementation, observation, evaluation and reflection stages. Research data in the form of student learning outcomes was taken using multiple choice test techniques and descriptions. The average score obtained in cycle I was 76.07, in cycle II it increased to 80.00. While classical completeness was 67.85% in cycle I, in cycle II it increased to 85.71%. Meanwhile, the average score for students' science process skills in cycle I was 70.8 in the high category, in cycle II the average score for students' science process skills increased to 78.1 in the high category. The conclusion of this research is that NOS (Nature of Science) oriented learning can improve students' science process skills and understanding of concepts.